Indicazioni all’utilizzo del concentrato midollare nella chirurgia endoscopica del morbo di Haglund - Rota, A.; De Santis, P.; Rota, P. (Lo Scalpello - Journal, 2019)
AUTOLOGOUS BONE MARROW-DERIVED MESENCHYMAL STEM CELLS (MSCS) INDICATIONS FOR ENDOSCOPIC TREATMENT OF HAGLUND’S SYNDROME Surgical treatment in Haglund’s deformity involves removal of the dorsolateral part of the calcaneus up to the insertion of the Achilles tendon and the inflamed retrocalcaneal bursa. Traditionally treated with open surgery, after failure of the conservative treatment, there is increasing interest in a more minimally invasive approach to reduce complications and improve the rate and ease of recovery. The poor results of open surgical treatment may be due to incorrect indication for surgery, incomplete or aggressive bone resection, fibrosis, chronic tendinopathy, painful scars and numbness in the heel. The minimally invasive surgical technique by an endoscopic calcaneoplasty (ECP) could be an option to overcome some of these problems. The endoscopic technique include: patient prone, peripheral anesthesia, standard instruments. We have used the autologous bone marrow-derived mesenchymal cells (MSCs) obtained from iliac crest for severe Achilles tendonosis. The purpose of our study was to describe management of Haglund’s Syndrome, evaluate the effectiveness of a minimally invasive procedure, demonstrating the validity as well in the revisions of the open treatments in athletes. Adequate relief of symptoms is considered to be dependant on removing any osseous irritation to the Achilles insertion (bone resection), fibrolysis and using autologous bone marrow-derived Mesenchymal stem cells (MSCs) for severe Achilles tendonosis.